Beyond Allies: Men’s Transformative Role in Women’s Empowerment in Nepal – A Sociological Perspective - Shiwakoti, Sahara (Medha: A Multidisciplinary Journal, 2025)
This article analyzes the role of men in advancing women’s empowerment in Nepal from a feminist political economy perspective, using secondary data from academic studies, policy documents, and national statistics. The approach recognizes that gender inequality is embedded in interconnected economic, political, and social systems shaped by patriarchy and crony capitalism. The study explores how men’s engagement—ranging from advocacy for gender-equitable policies to the redistribution of unpaid care work—can support women’s economic autonomy and political participation. It highlights that such involvement can be transformative when it challenges structural barriers related to class, caste, and ethnicity. However, the analysis warns against tokenistic or instrumental male participation that reinforces existing power hierarchies. Findings suggest that meaningful male engagement requires both structural reforms and cultural shifts that dismantle patriarchal norms. By situating men as complementary actors in the struggle for gender justice, the article underscores the importance of aligning individual attitudes with systemic change for sustainable women’s empowerment in Nepal.